Hubungan Tingkat Pendidikan Serta Usia Terhadap Pengetahuan Penggunaan Obat Analgesik dan Antipiretik pada Ibu Hamil di Puskesmas Gayamsari - Purnami, Islina Dewi; Ulfa, Yulinda Aini (Indonesian Journal of Medical and Pharmaceutical Science, 2024)
Background: Pain during pregnancy needs to be handled properly because pain that affects physically and psychologically pregnant women can cause depression and anxiety. Analgesic drugs are the most commonly given drugs worldwide and most analgesics are sold freely so do not require a prescription. The aim of this study was to determine the effect of education level and age on knowledge and consumption of analgesic and antipyretic drugs in pregnant women to reduce the risks posed during pregnancy and lactation. Methods: The study was conducted cross-sectionally at the Gayamsari Health Center in Semarang City. The sampling method used is purposive sampling. The instrument used is a questionnaire consisting of a knowledge questionnaire and a questionnaire on the use of analgesic and antipyretic drugs in pregnant women. The study sample was pregnant women who came and visited the Gayamsari Health Center and met the inclusion criteria. Results: The level of knowledge of pregnant women regarding analgesic and antipyretic drugs consumed during pregnancy is in the “High” category with a percentage of 80.0% and the results of the use of analgesic and antipyretic drugs in pregnant women show that respondents already understand well. Conclusion: Age did not affect the level of knowledge of pregnant women about analgesic and antipyretic drugs with a p-value of 0.216 where the p-value was greater than the significance level (α=5%). Correlation analysis also found that there was no significant relationship between recent education and the level of knowledge of pregnant women (p = 0.981 > 0.05).